Correlation between Atherogenic Index of Plasma and Lipid Profile with Cognitive Function and Their Effect on Outcome in Ischemic Stroke Patients - Fasihah Irfani Fitri; Muhammad Zulfikri (Faculty of Medicine Universitas Indonesia, 2023)
Dyslipidemia is one of the main risk factors for both ischemic stroke and cognitive impairment. Atherogenic index of plasma (AIP) has been shown to correlate with mortality and clinical outcomes in stroke, but studies about its association with cognitive impairment in ischemic stroke is still limited. We aimed to determine the correlation between AIP and lipid profile and cognitive function and their effect on outcome in ischemic stroke patients. A cross-sectional study involving 50 ischemic stroke patients in the Haji Adam Malik General Hospital was conducted from August 2021 to March 2022. We measured the cholesterol level and calculated the AIP then divided them into 3 risk categories which were high (AIP>0.21); intermediate (AIP>0.11and ≤0.21) and low (≤0.11). We performed cognitive assessment and stroke outcome at the 7th day of stroke onset. Data analysis was conducted with Spearman correlation test. The subjects were predominantly male (60%) with median age of 55 (34-68) years. Most of the subjects had AIP level of high risk (54%) and were cognitively impaired (66%). There was no significant association between AIP and both global cognition and each cognitive domain. However, there were significant negative correlations between total cholesterol (r=-0.31, p=0.03) and LDL-C level (r=-0.30, p=0.03) and attention. There was also a significant negative correlation between cognitive function and stroke outcome (r=-0.61, p=0.01). Higher total cholesterol and LDL-C levels showed negative correlation with cognitive function, mainly attention. Poorer cognitive function correlated with worse outcome in ischemic stroke patients.